Math 341

Proof by Induction

Mathematical Induction, or “induction” is a technique to prove a list of mathematical statements

P1,P2,P3,,Pn,Pn+1,,P_1, P_2, P_3, \dots, P_n, P_{n+1}, \dots,

Here each PnP_n stand for a mathematical statement. Example: PnP_n could be the statement

One way to prove that each PnP_n is true is to try to prove them one by one

and so on. The idea of mathematical induction is that once you have proved P1P_1, P2P_2, …, PnP_n, you know that P1P_1, P2P_2, …, PnP_n are true so you could use that knowledge when you try to prove Pn+1P_{n+1}.

An induction proof then always consists of the following steps:

  1. The initial case: a proof that P1P_1 is true
  2. The induction step: assuming that P1,,PnP_1, \dots, P_n are true, prove Pn+1P_{n+1} is true.

The example: prove 1+2+3++n=12n(n+1)1+2+3+\cdots+n = \frac12 n(n+1) for all nn

In the above example the initial step requires us to prove “1+2+3++n=12n(n+1)1+2+3+\cdots+n = \frac12 n(n+1)” when n=1n=1. For n=1n=1 the statement is

P1:1=121(1+1)P_1:\quad 1 = \frac12 \cdot1\cdot(1+1)

which is true, by direct calculation.

In the induction step we assume that

Pn:1+2+3++n=12n(n+1) P_n:\quad 1+2+3+\cdots+n = \frac12 n(n+1)

is true, and we have to prove

Pn+1:1+2+3++n+(n+1)=12(n+1)((n+1)+1).P_{n+1} : \quad 1+2+3+\cdots+n + (n+1) = \frac12 (n+1)\bigl((n+1)+1\bigr).

This step requires some algebra:

1+2+3++n+(n+1)=12n(n+1)+(n+1)(use Pn)=(12n+1)(n+1)(factor)=12(n+2)(n+1)=12(n+1)((n+1)+1)\begin{aligned} 1+2+3+\cdots+n + (n+1) &= \frac12 n(n+1) + (n+1) &\text{(use $P_n$)} \\ &= \left(\frac12 n+1\right)(n+1) &\text{(factor)}\\ &= \frac12 (n+2)(n+1)\\ &= \frac12 (n+1)\bigl((n+1)+1\bigr) \end{aligned}

So we have shown Pn    Pn+1P_n\implies P_{n+1} for any nNn\in \N: this is called the induction step.

The induction step gives us the chain of implications

P1    P2    P3    P4    P_1\implies P_2\implies P_3\implies P_4\implies \cdots

and since we have checked that P1P_1 is true, it follows that all PnP_n are true.